Analysis of the Economic Value of Environmental Services of Mangrove Ecosystem in Cendi Manik, Sekotong District, West Lombok Regency - Nuryadin, Rusmin; Fitria, Syawalina; Alim, Sahrul; Wahyudi, Rhojim; Amir, Sadikin; Valentino, Niechi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The area of mangrove ecosystems in West Nusa Tenggara Province continues to decline each year. One of the threatening factors that substantially contribute to such condition is socioeconomic activities of human beings in fulfilling their needs. An effort that can be made primarily to preserve the mangrove ecosystem is to quantify the economic value of environmental services provided by the mangrove ecosystem as a whole, so that the existence and sustainability of the mangrove ecosystem could be maintained. This research aims to calculate the total economic value of mangrove ecosystem services which indicate the four categories of ecosystem services including supporting services, provisioning services, regulatory services and cultural services. The research was carried out using a survey method by collecting data and information from location of this study to obtain actual data regarding the existence of the mangrove ecosystem. The results of the analysis show that the total economic value of mangrove ecosystem environmental services is 963,888,060/year. This value is divided into provider services (supply services) amounting to Rp. 153,002,250, regulatory services (arrangement services) Rp. 598,339,702, supporting services (support services) Rp. 2,243,250, and cultural services (cultural services) Rp. 210,308,857. The magnitude of the total economic value of mangrove ecosystem environmental services can be a reference for the government in determining compensation for services if there is degradation to mangrove ecosystem resources in the area.